A Novel Model for Securing Mobile-based Systems against DDoS Attacks in Cloud Computing Environment - El-Sofany, Hosam; Abou El-Seoud, Samir (International Journal of Interactive Mobile Technologies (iJIM), 2019)
the increasing growth of mobile devices technology and Mobile-based systems with the emerging of cloud computing technology, created a Mobile Cloud Computing field to be the recent future technology for different wireless services. The development of Mobile-based system under cloud computing environment solve some performance and environment related issues include: bandwidth, storage capacity, availability, scalability and heterogeneity. The Mobile-based cloud computing apps are different comparing to mobile computing apps, since in the first model the devices run cloud based web applications not as mobile computing native apps. Services of Mobile-based systems via cloud are accessing and sharing through internet connection thus they are open for attacker to attack on its security. Distributed Denial of Service (DDoS) attacks can cause a big problem in mobile cloud computing security. The main objective of DDoS attacks is to infect wireless devises resources (e.g., software applications, wireless network, etc.) and make them unavailable to the authorized user. In DDoS, the attacker tries to overload the Mobile-based service with traffic. The main objective of this research paper is to introduce novel model for securing Mobile-based systems against DDoS attacks. Efficiency and performance analysis evaluations of the proposed model are presented.  The feedbacks of the experimental results were highly promising, for protecting mobile-based cloud computing systems against DDoS attacks.